“Nothing to lose and the possibility of gaining”: a qualitative study on the feasibility and acceptability of registry-based randomised controlled trials among cancer patients and clinicians - Khic-Houy Prang; Bill Karanatsios; Angela Zhang; Ebony Verbunt; Hui-li Wong; Vanessa Wong; Lucy Gately; Ben Tran; Peter Gibbs; Margaret Kelaher (Trials, 2023)
Abstract Background Randomised controlled trials (RCTs) are considered the “gold standard” for evaluating the effectiveness of interventions in clinical research. However, conventional RCTs are typically complex, expensive, and have narrow eligibility criteria, which limits generalisability. Registry-based randomised controlled trials (RRCTs) are an alternative approach that integrates the internal validity of an RCT with the external validity of a clinical registry by recruiting real-world patients and leveraging an existing registry platform for data collection. As RRCT is a novel research design, there has been limited research on the feasibility and acceptability of RRCTs from the patients’ and trial team’s perspectives. This study aims to explore patients’, clinicians’, and study coordinators’ perspectives towards participation in and conduct of oncology RRCTs in Australia. Methods Thirty-seven semi-structured interviews were conducted with 15 cancer patients, 15 clinicians, and 7 study coordinators. Interviews were audio-recorded and transcribed verbatim. The data were analysed using thematic analysis. Results Three overarching themes were identified: (1) enablers and barriers to recruitment and enrolment of patients in RRCTs, (2) experiences of patients participating in RRCTs, and (3) recommendations for the implementation of future RRCTs. For patients, altruism and “trust in the clinician” were key reasons to participate in a RRCT. For clinicians and clinical trial coordinators, the RRCT study design was perceived as “simple and straightforward” but “less exciting” than RCTs. Competition from commercially sponsored RCTs poses challenges for investigator-led RRCTs recruitment, particularly if eligible patient numbers are low. There were limited impacts on patients’ treatment experiences and clinicians’ clinical workflow given that the RRCTs explored different standards of care. Recommendations to improve the enrolment of patients in RRCTs included generating greater buy-in from clinicians by increasing awareness of RRCTs via education initiatives and broader promotion of the “selling point” of RRCTs and providing monetary compensation to hospitals for enrolling patients. Conclusions Whilst patients, clinicians, and study coordinators were generally supportive of RRCTs, several barriers to effective RRCT implementation in oncology were identified. Developing strategies to increase acceptance of the methodology by clinicians will help enhance the uptake of RRCTs in Australia and internationally.